2006
DOI: 10.1038/sj.onc.1209236
|View full text |Cite|
|
Sign up to set email alerts
|

ASPP1, a common activator of TP53, is inactivated by aberrant methylation of its promoter in acute lymphoblastic leukemia

Abstract: We have analyzed the regulation and expression of ASPP members, genes implicated in the regulation of the apoptotic function of the TP53 tumor-suppressor gene, in acute lymphoblastic leukemia (ALL). Expression of ASPP1 was significantly reduced in ALL and was dependent on hypermethylation of the ASPP1 gene promoter. Abnormal ASPP1 expression was associated with normal function of the tumor-suppressor gene TP53 in ALL. The analyses of 180 patients with ALL at diagnosis showed that the ASPP1 promoter was hyperme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 29 publications
2
49
2
Order By: Relevance
“…Methylation-(M) and unmethylation (U)-sensitive primers, as listed in Table 1, were designed to amplify the promoter region (À681 to À476) of ASPP1 (GeneBank NM 015316) according to a previous study 16 for MS-PCR analysis. Universal methylated DNA (Chemicon, Atlanta, GA, USA) and water blanks without template were used as positive and negative controls for each PCR set, respectively.…”
Section: Dna Preparation Sodium Bisulfite Modification and Ms-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation-(M) and unmethylation (U)-sensitive primers, as listed in Table 1, were designed to amplify the promoter region (À681 to À476) of ASPP1 (GeneBank NM 015316) according to a previous study 16 for MS-PCR analysis. Universal methylated DNA (Chemicon, Atlanta, GA, USA) and water blanks without template were used as positive and negative controls for each PCR set, respectively.…”
Section: Dna Preparation Sodium Bisulfite Modification and Ms-pcrmentioning
confidence: 99%
“…Recently, it has been demonstrated that ASPP1 is downregulated in human cancer cell lines expressing wild-type p53, 14,15 including breast cancer and acute lymphoblastic leukemia. 11,16 Hypermethylation of gene promoter or the 5 0 untranslated region was shown to be a possible epigenetic mechanism that inactivates ASPP1. 14,16 In this study, we evaluated the expression and methylation profiles of ASPP1 in normal placentas and gestational trophoblastic disease in correlation with clinical parameters, followed by an in vitro functional analysis, in an attempt to unveil the possible role of ASPP1 in the pathogenesis of gestational trophoblastic disease.…”
mentioning
confidence: 99%
“…In many cancers, ASPP1 and ASPP2 have been found to be down-regulated by promoter methylation [48,49]. For example, reduced ASPP1 expression by promoter methylation is associated with high relapse rate and mortality in acute lymphoblastic leukaemia [48]. Down-regulation of ASPP2 in diffuse large B-cell and follicular centre lymphoma is also associated with poor prognosis [47].…”
Section: Restoring P53 Function By Preventing Iaspp and Mdm2 From Inhmentioning
confidence: 99%
“…ASPP1 and ASPP2 are transcriptional targets of E2F1, a key transcription factor that promotes cell cycle G1 to S phase transition. In many cancers, ASPP1 and ASPP2 have been found to be down-regulated by promoter methylation [48,49]. For example, reduced ASPP1 expression by promoter methylation is associated with high relapse rate and mortality in acute lymphoblastic leukaemia [48].…”
Section: Restoring P53 Function By Preventing Iaspp and Mdm2 From Inhmentioning
confidence: 99%
“…12,13 Full clinical and laboratory data were available for 39 T-ALL and 145 B-ALL patients (one of them lacking survival data) with a median age of 11.5 years (range 0.5-87 years), including 100 children under 15 years of age (median 5.5 years, range 0. [5][6][7][8][9][10][11][12][13][14] and 84 patients over 15 years of age (mean age 34.5, range 15-87). Sample collection was approved by the individual institutional review boards of the participating institutions and informed consent was obtained from all adult patients and children's parents or legal guardians.…”
Section: Patients' Samples and Cell Linesmentioning
confidence: 99%